THE CONCEPT OF DIPLOMACY AND ITS HISTORICAL DEVELOPMENT - Ergasheva Feruzabonu Odiljonovna (TADQIQOTLAR.UZ, 2025)
Diplomacy, the art and practice of conducting negotiations between representatives of states, is a cornerstone of international relations. Its evolution reflects the complexities of human interaction and the shifting dynamics of power across centuries. This article explores the historical development of diplomacy, from its ancient roots to its modern manifestations.